Examining priorities and investments made through the Global Financing Facility for maternal and newborn health: a sub-analysis on quality - Meghan Bruce Kumar; Mary Kinney; Joël Kiendrébéogo; Donat Shamba; Joy E. Lawn; Peter Waiswa (Global Health Action)
Improving quality of care could avert most of the 4.5 million maternal and neonatal deaths and stillbirths that occur each year. The Global Financing Facility (GFF) aims to catalyse the national scale-up of maternal and newborn health (MNH) interventions through focused investments. Achieving impact and value for money requires high, equitable coverage and high quality of interventions. This study examines whether the rhetoric of increasing coverage together with quality has informed investment strategies in MNH through a secondary analysis of 25 GFF documents from 11 African countries. The analysis shows that the country GFF-related documents incorporate some MNH-related quality of care components; however, there is a lack of clarity in what is meant by quality and the absence of core MNH quality of care components as identified by the World Health Organization’s MNH quality framework, especially experience of care and newborn care. Many of the Investment Cases have a more diagonal focus on MNH service delivery considering the clinical dimensions of quality, while the investments described in the Project Appraisal Documents are primarily on horizontal structural aspects of the health system strengthening environment. The GFF is at the forefront of investing in MNH globally and provides an important opportunity to explicitly link health systems investments and quality interventions within the MNH continuum of care for optimal impact.